Some addition to the Hyphomycetes from India - A.N. RAI*, SMITA JAIN and (Indian Phytopathology, 2004)
This paper deals with the three new species of Alternaria Nees ex Fr. viz., A. aracearum on Raphidophora pertusa Scht. (Aracaceae), A.bundelkhandae on Leucaena leucocephala (Lam.) De wit.(Mimosaceae), and A.cryptostegiae on Cryptostegia grandiflora R.Br. (Asclepiadaceae) collected from forest plants of Madhya Pradesh. The new fungal forms were described , illustrated and compared with allied taxa.